POTENSI DAN STATUS KONSERVASI IKAN DI BENDUNGAN LAKITAN KABUPATEN MUSI RAWAS, PROVINSI SUMATERA SELATAN - Dian Samitra; Zico Fakhrur Rozi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to determine the potential and conservation status of fish in Lakitan Dam Musi Rawas Regency. This research was conducted in February until April 2018. The location of the research was determined by using purposive sampling technique. The samples were collected by using scatter nets and the subsequent identification was done in the Biology Laboratory of STKIP PGRI Lubuklinggau. Conservation status data is determined by IUCN Redlist while fish potential data is obtained from interview with the surrounding community. A total of 17 fish species were found during the study, divided into categories not evaluated 8 species (47%), 8 species (47%) least concern and 1 species (6%) data deficient. While the potential of fish as fish consumption as many as 12 species (62%), 3 species (23%) ornamental fish as well as fish consumption and ornamental fish as many as 2 species (15%). Keywords: Lakitan Dam, Potential Fish, Conservation Status